Characteristics of Head Nurse as Perceived by Health Care Team at Police General Hospital - คงชินศาสตร์ธิติภาวินีย์ (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this descriptive research was study characteristics of Head nurse as perceived by health care team at Police General Hospital. There were 3 characteristics, leadership professional’s nurse and management. The study sample were health care team at Police General Hospital including 247 nurses, 59 manager’s nurses and 148 doctor. The instruments was a rate scale on frequency of characteristics of head nurse. Data were collected by questionnaire. The validity of the questionnaire was conducted by 3 experts and the Cronbach’s alpha coefficient was.98. Data were analyzed by using mean, standard deviation, one way ANOVA. The results of this study were as follow: 1. The characteristics of head nurse as perceived by health care team at Police General Hospital were revealed high. When considered in each aspect, it was found that leadership was revealed highest. 2. The comparison on the mean level of the overall characteristics of Head nurse as perceived by health care team at Police General Hospital was found significant at the P < .05 level.